2021
DOI: 10.3390/land10080793
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use and Land Cover Changes on Urban Ecosystem Service Value in Dhaka, Bangladesh

Abstract: Urban ecosystem services provide a wide range of services to sustain life, social relation, health, etc., and address most of the challenges, including climate change and environmental pollution. While it is recognized that the urban ecosystem substantially contributes to human well-being in cities, there is less attention to consider the value of urban ecosystem service in urban planning and policymaking. This study analyzed the land use and land cover (LULC) dynamics of city of Dhaka over the past three deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 83 publications
4
33
0
Order By: Relevance
“…The interactions between regional development processes and ecosystems have become the focus of the human-land relationship worldwide. Previous studies on regional development and ecosystem services have focused on the following three aspects: the impact of land use change and landscape pattern evolution on ESV and the response of ESV to land use degree [3,[13][14][15][16][17][18][19][20][21]; anthropogenic changes to the quantity, patterns, functions, and structures of land use through urbanization that affect ecosystem services or the relationship between urbanization and ecosystems [22][23][24][25][26][27][28][29][30][31]; and the formulation and implementation of spatial land planning, which raises awareness regarding the multiobjective development of urban space for society, economy, and ecology [32][33][34][35][36][37]. It is critical to consider ESV and spatial responses to regional sustainable development and optimize land resource management policies to improve ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between regional development processes and ecosystems have become the focus of the human-land relationship worldwide. Previous studies on regional development and ecosystem services have focused on the following three aspects: the impact of land use change and landscape pattern evolution on ESV and the response of ESV to land use degree [3,[13][14][15][16][17][18][19][20][21]; anthropogenic changes to the quantity, patterns, functions, and structures of land use through urbanization that affect ecosystem services or the relationship between urbanization and ecosystems [22][23][24][25][26][27][28][29][30][31]; and the formulation and implementation of spatial land planning, which raises awareness regarding the multiobjective development of urban space for society, economy, and ecology [32][33][34][35][36][37]. It is critical to consider ESV and spatial responses to regional sustainable development and optimize land resource management policies to improve ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Sannigrahi et al [9] discovered that decreases in forestland, wetland, and water areas, along with the expansion of built-up land, has resulted in a considerable decline in global ESs by measuring the global ESV and its response to land-use change from 1995 to 2015. Rahman et al [19] examined the effect of land-use and land-cover changes on the value of urban ESs in Dhaka, Bangladesh. They discovered that the growth of built-up land came at the expense of farmland, forestland, and water areas, and the regional ESV continued to decline.…”
Section: Introductionmentioning
confidence: 99%
“…A similar adverse effect of increasing imperviousness on bird richness is evident in Dhaka. During the last two decades, a rapid shift in land cover features in this city has been noted by several studies (Sultana et al 2009, Byomkesh et al 2012, Jaman et al 2020, Rahman and Szabó 2021. Because urbanization in Dhaka is messy, like in many other South Asian cities (Ellis and Roberts 2016), unplanned expansion has already resulted in a decline in the proportion of green spaces and water body areas (Appendix 4, Image A4.4; Sultana et al 2009.…”
Section: Bird Diversity Directly and Indirectly Affected By Land Cove...mentioning
confidence: 90%
“…In Dhaka, existing ecological research has mostly focused on land cover change (Sultana et al 2009, Byomkesh et al 2012, Jaman et al 2020, Rahman and Szabó 2021, climatic effects and environmental pollution (Dewan et al 2021, Uddin andJeong 2021), and economic and social aspects (Zinia and McShane 2018). Several such studies have reported that the high intensity of population growth and extent of human settlement https://www.ecologyandsociety.org/vol27/iss1/art19/ have already caused a significant alteration in abiotic conditions, deficiency in natural vegetation cover, and loss in green spaces and wetland areas in this city (Sultana et al 2009, Byomkesh et al 2012, Jaman et al 2020, Dewan et al 2021.…”
Section: Introductionmentioning
confidence: 99%